The outcome of control groups in clinical trials of conservative treatments for chronic mechanical neck pain: a systematic review - Vernon, Howard (BioMed Central, 2006)
BACKGROUND: Chronic neck pain is highly prevalent in Western societies, with about 15% of females and 10% of males suffering with it at any time. The course of untreated chronic neck pain patients in clinical trials has not been well-defined and the placebo effect has not been clarified. METHODS: A systematic review of RCT's of conservative treatments for chronic mechanical neck pain was conducted. Studies were excluded if they did not include a control group, if they involved subjects with whiplash injuries, a predominance of headache or arm pain associated with chronic neck pain and if only one treatment was reported. Only studies scoring 3–5 out of 5 on the Jadad Scale for quality were included in the final analysis. Data on change in pain scores of subjects in both placebo (PL) as well as no-treatment (NT) control groups were analyzed. Mean changes in pain scores as well as effect sizes were calculated, summarized and compared between these groups. RESULTS: Twenty (20) studies, 5 in the NT group and 15 in the PL group, with outcome intervals ranging from 1–52 weeks were included in the final analysis. The mean [95% CI] effect size of change in pain ratings in the no-treatment control studies at outcome points up to 10 weeks was 0.18 [-0.05, 0.41] and for outcomes from 12–52 weeks it was 0.4 [0.12, 0.68]. In the placebo control groups it was 0.50 [0.10, 0.90] at up to 10 weeks and 0.33. [-1.97, 2.66] at 12–24 weeks. None of the comparisons between the no-treatment and placebo groups were statistically significant. CONCLUSION: It appears that the changes in pain scores in subjects with chronic neck pain not due to whiplash who are enrolled in no-treatment and placebo control groups were similarly small and not significantly different. As well, they do not appear to increase over longer-term follow-up.